RESPONSIVITAS ADMINISTRASI KEPENDUDUKAN MELALUI PROGRAM PASCA AKAD NIKAH DI KOTA TASIKMALAYA - Riena Latifa; Vidya Imanuari Pertiwi (Journal Publicuho, 2025)
This study aims to analyse the responsiveness of public services through the PASUTRI Program (Post-Marriage: Husband and Wife Receive Family Cards and Electronic Identity Cards) at the Population and Civil Registration Office of Tasikmalaya City. The research method used is a qualitative approach with a case study design according to Creswell. Data were obtained through interviews, observations, and documentation. The findings of this study are 1) Officers provide services with a good attitude, politeness, and friendliness to the public, 2) Officers strive to issue Electronic Identity Cards (KTP-el) and Family Cards on the wedding day. However, challenges such as power outages, network disruptions, and server issues still occur. 3) The Standard Operating Procedures (SOP) have been consistently implemented. However, some people still prefer to use intermediaries in the marriage registration process at the Religious Affairs Office (KUA), 4) Document verification is carried out using the Simantap Pasutri application, although some challenges require further coordination, 5) The issuance of Electronic Identity Cards and Family Cards is carried out exactly on the wedding day, and 6) Public complaints are responded to through various media.